A Review on Transungal Patch for Effective Treatment on Nail Infection - Pote P. Yash; Dr. Sandeep C. Atram; Dr. Vikrant P. Wankhade; Dr. Nishan N. Bobade; Dr. Shrikant D. Pande (Asian Journal of Pharmaceutical Research and Development, 2026)
Transungual drug delivery presents a promising, targeted strategy for the treatment of nail conditions such as onychomycosis and nail psoriasis, effectively overcoming the limitations associated with traditional oral and topical therapies. The distinctive architecture of the nail creates substantial obstacles to drug penetration owing to its girth, limited permeability, and dense keratin composition. Recent progress in drug formulation—including the development of transungual patches, permeation enhancers, and nanocarrier systems—has enhanced the delivery of drugs to the nail bed and matrix, where the majority of pathologies are located. Transungual patches, in particular, offer sustained adhesion, regulated drug delivery, and improved patient adherence. Their efficacy and safety are assessed through a comprehensive analysis of physical, mechanical, and biological parameters, including uniformity of thickness and weight, folding endurance, tensile strength, surface pH, moisture content, drug content, drug release profile, permeation studies, antifungal activity, and stability. Although laboratory results are promising, additional clinical studies are necessary to refine the patch design, improve nail adhesion, and confirm its effectiveness and applicability in real-world applications.